A Modeling of Organizational Citizenship Behavior in Islamic Education Institution - Fauzi, Farid; Siahaan, Amiruddin; Nasution, Inom (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study analyzed the determinants of organizational justice, job satisfaction, and organizational commitment on organizational citizenship behavior (OCB) among MTsN teachers in Central Aceh Regency. Using a quantitative approach with a survey of 280 teachers, the data were analyzed through the Partial SEM-PLS approach. The population of this study consisted of all MTsN teachers in Central Aceh Regency, from which a sample of 280 respondents was determined using the simple random sampling technique to ensure representation across different madrasahs. The data sources included primary data obtained directly from respondents through structured questionnaires. The data collection technique employed a survey method using a Likert-scale questionnaire designed to measure teachers' perceptions of organizational justice, job satisfaction, organizational commitment, and OCB. The results showed that organizational justice (βz41 = 0.224), job satisfaction (βz42 = 0.399), and organizational commitment (βz43 = 0.243) had a positive and significant direct effect on OCB. Organizational justice also had a positive and significant effect on job satisfaction (βX21 = 0.667), while organizational justice (βY31 = 0.537) and job satisfaction (βY32 = 0.228) positively and significantly affected organizational commitment. The Goodness of Fit (GoF) value of 0.614 indicated a strong model. These findings emphasize the importance of organizational justice and job satisfaction in strengthening commitment and encouraging teacher OCB, which could serve as a foundation for developing sustainable policies and programs to improve madrasah performance.